Hidden of Human Potentials of Children with Down Syndrome (DS) Based on Response to Intervention - Bintoro, Totok; Riana Bagaskorowati; Murni Winarsih (LPPM Undiksha, 2022)
Every child has potential, both typical children and children with special needs, especially children with Down Syndrome (DS). Children with DS are classified as having mental retardation; a low level of intelligence indicates the most prominent characteristics. Children with DS have opportunities to grow and develop and possibilities in their human potential. This study aims to identify the hidden human potential in children with Down syndrome (DS) based on the response to the intervention. This type of research is a case study. Researchers chose three research subjects as samples to be observed. The approach used in this research is a case study with a qualitative descriptive approach through an experimental study method. Data collection methods in this study were interviews, observation, documentation, and field notes. The instruments used are observation sheets and interviews. The data used in this study is qualitative data with the Miles and Huberman model. The study results showed that three children with DS had shown the advantages of hidden human potential such as drawing and dancing. The emergence of this hidden human potential is shown by the creation of trust in their relationships with peers, parents, and teachers.